2015
DOI: 10.3733/ca.v069n03p150
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fuel treatments on California mixed-conifer forests

Abstract: Land managers implement forest fuel reduction treatments, including prescribed fire, mastication, and hand-and mechanical thinning, to modify wildfire behavior. Fuel treatments decrease tree density, increase mean canopy base height and remove surface fuels, and have been shown to reduce fire severity in yellow pine and mixed-conifer forests, even under relatively severe weather conditions. However, less is known about the impacts of fuel treatments on other facets of forest ecology. Synthesizing evidence from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
(94 reference statements)
0
5
0
Order By: Relevance
“…, Winford et al. ). However, the spatial footprint of active management will continue to be limited by economic, ecological, social, and political factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Winford et al. ). However, the spatial footprint of active management will continue to be limited by economic, ecological, social, and political factors.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term fire suppression in these fire-dependent ecosystems has greatly reduced fire occurrence but ironically increased the probability that the outcomes of fire will be ecologically negative when they occur (Steel et al 2015). Restoration of low tree densities and low fuel loadings in FRG I forests by managers can greatly increase forest resilience to fire and drought and benefit a suite of forest conditions, ecological processes, and biota (Schwilk et al 2009, Stevens et al 2014, Hanberry et al 2015, Winford et al 2015. However, the spatial footprint of active management will continue to be limited by economic, ecological, social, and political factors.…”
Section: Management Implicationsmentioning
confidence: 99%
“…By reducing surface litter and overstory shading and by moderately disturbing the soil, these treatments played a similar role as low‐ to moderate‐severity fire by increasing habitat for understory species. Previous work has suggested that fuel reduction treatments in YPMC forests rarely have negative impacts on plant diversity, and that positive impacts are more likely where fire is included in the treatment (Barefoot et al, 2019; Collins et al, 2007; Matzka & Kellogg, 1999; McIver et al, 2012; Winford et al, 2015). Our results support this generalization, as in our study plant diversity was higher in areas burned at low‐moderate severity (i.e., locations that were both thinned and burned) than in areas thinned but not burned (managed portion of the unburned class).…”
Section: Discussionmentioning
confidence: 99%
“…Field studies within the Sierra Nevada Mountain Range broadly, and in the Lake Tahoe Basin specifically, have demonstrated the effectiveness of thinning and burning treatments in moderating impacts of wildfires through reductions in surface fuels, ladder fuels, and canopy contiguity (Safford et al 2009, Winford et al 2015. LANDIS-II modeling indicated that mechanical thinning would moderate fire behavior more effectively than hand thinning, which is limited to smaller trees; this finding was Represents fine sediment and nutrient loading to streams and lakes compared to baseline conditions.…”
Section: Complementary Work That Informed Assumptions In the Analysis...mentioning
confidence: 96%